Instructional- Learning design based on the load of cognitive theory of the achievement of mathematics and spatial / visual intelligence among the students of the second intermediate class in middle school students - Iraq - Mekki, Abdul Wahid Mahmoud Mohammed (Arab Journal for Sciences and Research Publishing, 2016)
The research aims to know the effectiveness of Instructional- Learning design according to the load of cognitive theory of the achievement and spatial / visual intelligence for students of the second intermediate class in mathematics. The sample of the research consists of (59) students, distributed randomly into two equal groups, in variables of (age measured in Months, Visual intelligence, and prior achievement Mathematics degrees in the first semester of the academic year exam (2015-2016).The first experimental groups has been studied according to the Instructional Designing consist of (30) students, and the second group (control group) which contains (29) students has been taught by the normal method. Two research tools have been conducted. The first one is for measuring the student’s achievement, consisting of (20) items, and the other for measuring spatial / visual intelligence contains (25) paragraph. The veracity and constancy of the two test has been checked. The data were analyzed then by using T-test. The results of the research reveal the following. There are statistical significant difference between the two sets of research students (experimental and control) and in favor of the experimental group in the achievement test and in the spatial / visual intelligence test. According to the results in this work, the researcher’s recommended use of educational design according to load cognitive in the teaching of mathematics because of its theoretical effect to increasing student’s achievement, and emphasis mathematician to use colors when they draw geometric shapes or write to the colors of a positive impact in keeping the information and saved easily remember.